Universities and Innovation: University Relevance and Engagement Are More Likely Where Public Governance Is Strategic - JOYCE, Paul (Transylvanian Review of Administrative Sciences, 2024)
The paper opens with a consideration of the functions of universities and the idea of public policy promoting linkages between universities and businesses to support innovation and economic growth. This is followed by a section outlining the concept of a ‘strategic state’ and original analysis using data from the Institutional Profiles Database for 2016 on 63 countries. This analysis reveals a statistical association of (i) university relevance to business needs, and (ii) university engagement with firms. It is noted that this is consistent with the existence of reciprocal causation – greater university relevance encourages engagement with firms, and engagement with firms fosters university relevance. Next, the analysis shows that countries that had governments with strong strategic state characteristics and universities that were relevant and engaged with business firms were statistically associated with greater societal capacities for technological adaptation and innovation. The paper concludes by considering strategically governed universities. Several suggestions are made, including one that public policy should aim for universities to have strategic autonomy and another that central government (in a spirit of cooperation and partnership) supports local government, local businesses, and universities in their efforts to create and operate locally focused collaborations to innovate and bring about economic development.